Nuclear Lamins and Oxidative Stress in Cell Proliferation and Longevity - Shimi, Takeshi (Adv Exp Med Biol, 2014)
In mammalian cells, the nuclear lamina is composed of a complex fibrillar network associated with the inner membrane of the nuclear envelope. The lamina provides mechanical support for the nucleus and functions as the major determinant of its size and shape. At its innermost aspect it associates with peripheral components of chromatin and thereby contributes to the organization of interphase chromosomes. The A- and B-type lamins are the major structural components of the lamina, and numerous mutations in the A-type lamin gene have been shown to cause many types of human diseases collectively known as the laminopathies. These mutations have also been shown to cause a disruption in the normal interactions between the A and B lamin networks. The impact of these mutations on nuclear functions is related to the roles of lamins in regulating various essential processes including DNA synthesis and damage repair, transcription and the regulation of genes involved in the response to oxidative stress. The major cause of oxidative stress is the production of reactive oxygen species (ROS), which is critically important for cell proliferation and longevity. Moderate increases in ROS act to initiate signaling pathways involved in cell proliferation and differentiation, whereas excessive increases in ROS cause oxidative stress, which in turn induces cell death and/or senescence. In this review, we cover current findings about the role of lamins in regulating cell proliferation and longevity through oxidative stress responses and ROS signaling pathways. We also speculate on the involvement of lamins in tumor cell proliferation through the control of ROS metabolism.